Maximizing the Value of Information Technology Investment based on Strategic Alignment, Risk Control and Real OptionsA Case Study of Enterprise System Implementation at PT. Pegadaian (Persero) - Mulyana, Rahmat; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2012)
The world of IT market has experienced fast growth by9.7% worth US 527.9 billion (Rp 5.015,1 trillion) in 1995, but still IT value realization is questioned with the advent of IT Productivity Paradox phenomenon. In 2002, Gartner survey stated that 20 to 70% IT investment worth US 600 billion (Rp6,315.8 Ã‚Â trillion)Ã‚Â wasÃ‚Â wasted. Ã‚Â However, Ã‚Â the Ã‚Â phenomenon Ã‚Â was fadingÃ‚Â with theÃ‚Â riseÃ‚Â of Ã‚Â IT governanceÃ‚Â and Ã‚Â management Ã‚Â field, including IT investment management best-practice. Latest research from PwC and ITGI in 2011 has shown that the practiceÃ‚Â brought 27.1% increased value and 28.1% improved business competitiveness. Recently, PT. Pegadaian (Persero) has planned to invest on a new centralized real-time online Enterprise System. Considering this is a large scale IT investment which estimatedÃ‚Â TCO is around Rp 1.1 trillion (16% of Total Gross Revenue andÃ‚Â 1100% of Total Investment in 2011), while the world historical data has shown many of its failures, in fact Pegadaian itself has experienced ES implementation failure in 2009-2011 which has wasted significant resources, therefore the management is veryÃ‚Â concernedÃ‚Â Ã‚Â aboutÃ‚Â Ã‚Â howÃ‚Â Ã‚Â toÃ‚Â Ã‚Â preventÃ‚Â Ã‚Â projectÃ‚Â Ã‚Â failuresÃ‚Â Ã‚Â while maximizing the value from it. The author has proposed the combination use of strategic alignment, risk control and real options valuation methods which enhanced the conventional investmentÃ‚Â analysis Ã‚Â methods Ã‚Â such Ã‚Â asÃ‚Â IRR,Ã‚Â NPV,Ã‚Â ROI Ã‚Â and Payback Period to solve PegadaianÃ¢â‚¬â„¢s problem. This paper result showed that the combination of those methods has maximized the value of IT investment by making sure that the investment is aligned with business objectives, able to control its risks and offered managerial flexibility through viable investment option configurations which maximizing the value. Keywords: IT investment, strategic alignment, risk,Ã‚Â real options, enterprise systems, IT governance and management